2015
DOI: 10.1142/s0219633615500303
|View full text |Cite
|
Sign up to set email alerts
|

DFT/TD-DFT study of the structural and spectral properties of two forms of Rhodamine B

Abstract: The absorption wavelengths of the two forms of Rhodamine B, cation and zwitterion, were investigated by Time-Dependent Density Functional Theory (TD-DFT) in combination with polarizable continuum model. The redshift in absorption spectrum of cation relative to zwitterion is attributed to strong inductive e®ect of carboxyphenyl group and weak electrostatic repulsion between xanthene ring and carboxyphenyl group. The absorption wavelengths of cation and zwitterion decrease linearly with increase of solvent polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several researchers have reported the potential structures of RhB in aqueous solution under synthesis conditions, whereas MO is known to ionize (SO 3 – + Na + ) and exist in negatively charged forms in solutions . Chi et al reported the optimized molecular structures and the relative Gibbs free energy of the zwitterion and cation of RhB in water and demonstrated that the cations were more stable forms than the zwitterion.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have reported the potential structures of RhB in aqueous solution under synthesis conditions, whereas MO is known to ionize (SO 3 – + Na + ) and exist in negatively charged forms in solutions . Chi et al reported the optimized molecular structures and the relative Gibbs free energy of the zwitterion and cation of RhB in water and demonstrated that the cations were more stable forms than the zwitterion.…”
Section: Resultsmentioning
confidence: 99%
“…There are effective structures inside DNBT , DNAF , and DNTO that provide favorable conditions for energy level transitions; in particular, the large conjugated ring structure in DNTO enables a large number of π–π* transitions to be realized, so the absorption peak is the strongest, while the NN bond in DNAF as the furazan connection is a very effective chromophore. , There are not only π–π* transitions but also n−π* transitions inside DNAF , and because the n-orbital energy level is the highest, this is also an important factor that λ max for DNAF is greater than DNBT and DNTO . The nitro group, as a strong absorption band auxochrome caused by the n−π* jump, provides strong evidence for the red shift of the small absorption peak where next to the maximum absorption peak of DNAF and DNTO . Additionally, because each compound has a maximum absorption rate at specific wavelengths of 225, 228, and 201 nm, it can be predicted that there will be ultraviolet absorption in the secondary light region (region III in Figure ) and exhibit potential possibility of fluorescence excited state.…”
Section: Resultsmentioning
confidence: 99%